Small Incision Lenticule Extraction for Correction of Myopia and Myopic Astigmatism: First 24-Hour Outcomes. (7th June 2017) - Liu, Taixiang; Dan, Tingting; Luo, Yan
Abstract : Purpose . To observe the first 24-hour (h) outcomes of the small incision lenticule extraction procedure (SMILE) for myopia and myopic astigmatism. Methods . Fifty-three eyes (27 patients) scheduled for SMILE were followed immediately (0 h), 2, 4, 6, and 24 h after SMILE. Uncorrected visual acuity (UCVA), conjunctival congestion, pain level, and corneal edema, thickness, and densitometry were recorded. Results . At 2 h after SMILE, 15.1% of eyes had ≤0.1 LogMAR UCVA; this increased to 62.3%, 98.1%, and 100% at 4, 6, and 24 h, respectively. Some eyes (33.96%) had mild corneal edema immediately after surgery. No 6 h postoperative edema was observed. In the first 24 h after SMILE, corneal thickness gradually decreased. Postoperative corneal densitometry values were significantly higher than preoperative values but gradually decreased during the first postoperative 24 h. Conclusions . In the first postoperative 24 h, UCVA and corneal status (edema and densitometry) improved quickly.